UPAYA PENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1 SEKOLAH DASAR MENGGUNAKAN MODEL PROJECT BASED LEARNING (PJBL) - Anisa Pramudita (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
This study addresses the low early reading skills among first-grade elementary students, which are often caused by monotonous teaching methods and the lack of engaging learning media. The aim of this research is to evaluate the impact of the Project-Based Learning (PjBL) model on improving reading abilities at SDN Karang Mekar Mandiri 1. A quantitative approach was applied involving 32 students, with data collected through pre-tests, post-tests, evaluation sheets, and closed-ended questionnaires. The results showed an increase in the average score from 67.65 to 80.25, with 84.53% of students showing improvements in reading skills and learning motivation. The PjBL model proved to be an effective and innovative approach for enhancing early reading abilities and fostering active student participation in the learning process.